1995
DOI: 10.1002/ijc.2910610420
|View full text |Cite
|
Sign up to set email alerts
|

Expression of protectin (CD59) in human melanoma and its functional role in cell‐ and complement‐mediated cytotoxicity

Abstract: Immunohistochemical and/or indirect immunofluorescence analysis with monoclonal antibody (MAb) H19 demonstrated the expression of protectin (CD59) in 54 surgically removed metastatic melanoma lesions and on 8 out of 12 melanoma cell lines. CD59 expression had a low degree of intra- and intertumor heterogeneity. SDS-PAGE analysis showed that the molecular weight of CD59 expressed on melanoma cells is about 20 kDa. Treatment of melanoma cells with 5U/ml of phosphatidylinositol-specific phospholipase C completely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 23 publications
0
27
0
Order By: Relevance
“…The expression of CD55 and CD59 was enhanced on renal clear cell carcinomas as compared with their expression on PTEC. Also other studies on RCC (Niehans et al, 1996), melanoma (Brasoveanu et al, 1995), and lung cancer (Varsano et al, 1995) observed an enhanced expression of CD55 and/or CD59. In contrast to the results of the study of Niehans et al (1996), who detected a focal moderate expression of CD55 on the interface between tumor cell nests and stroma, we were able to detect weak homogeneous membrane expression on CD55-positive renal tumor cells by immunohistochemistry.…”
Section: Discussionmentioning
confidence: 72%
“…The expression of CD55 and CD59 was enhanced on renal clear cell carcinomas as compared with their expression on PTEC. Also other studies on RCC (Niehans et al, 1996), melanoma (Brasoveanu et al, 1995), and lung cancer (Varsano et al, 1995) observed an enhanced expression of CD55 and/or CD59. In contrast to the results of the study of Niehans et al (1996), who detected a focal moderate expression of CD55 on the interface between tumor cell nests and stroma, we were able to detect weak homogeneous membrane expression on CD55-positive renal tumor cells by immunohistochemistry.…”
Section: Discussionmentioning
confidence: 72%
“…29 CD59 prevents cytolysis by binding to C8 and C9 and by inhibition of the C9-polymerization process. 30 Expression of these membrane complement regulators has been described for many tumors as well as for tumor cell lines of different origin, e.g., colon carcinoma, 31,32 melanoma, 33 breast carcinoma, 25 ovarian carcinoma 34 and tumors of the hematopoietic system. 35,36 Cumulative evidence supports the notion that membrane complement regulatory proteins are expressed in higher quantities in malignant tissue than in normal tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Barriers for free access of MAbs and C to the tumour cells and the existence of C resistance mechanisms may limit the success rate (Riethmuller et al, 1993). However, in vitro tests have shown that it is possible to kill tumour cells in suspension using appropriate MAbs and C in combination with targeted neutralization of membrane regulators of complement (Cheung et al, 1988;Bj0rge et al, 1994;Hakulinen and Meri, 1994;Junnikkala et al, 1994;Brasoveanu et al, 1995;Maenpaa et al, 1996). The in vivo protocols for this type of immunotherapeutic analysis therefore have to be refined for effective destruction of tumour cells in three-dimensional structures.…”
Section: Sensitivity Of Pa-1 Cells and Spheroids To C-mediated Cytotomentioning
confidence: 99%
“…Most in vitro studies on the expression and function of C regulators on malignant cells have used cell suspensions and/or monolayer cell cultures (Cheung et al, 1988;Bj0rge et al, 1994;Hakulinen and Meri, 1994;Junnikkala et al, 1994;Brasoveanu et al, 1995;Maenpaa et al, 1996). In many respects, these systems are markedly different from the actual conditions in solid tumours in vivo (Miiller-Klieser, 1987).…”
mentioning
confidence: 99%